Pengaruh Pemberian Kompos Pelepah Kelapa Sawit Dengan Berbagai Dekomposer Terhadap Pertumbuhan dan Hasil Tanaman Pakchoy (Brassica Chinensis L) - Susi sundari; Murniati '; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Pakchoy plants is one kind of vegetables that have commercial value and contains nutrients that are essential to the human body so favored by many people. Research is aimed to know the influence compost palm oil frond with decomposer which gives growth and yield good pakchoy held in greenhouse the Faculty of Agriculture University of Riau for three months that is October until December 2011. The draft used are thoughts of random complete which consists of three and six deut treatment which D1 (Mikroorganism local), D2 (Trichoderma sp) dan D3 (EM-4). Based on the research has been done suggest that composting of palm frond with some decomposers in plants pakchoy results were not significantly different with plant height, number of leaves, leaf area, fresh weigt and root volume. Of this research, the plant pakchoy treated EM-4 decomposers tends to give a higher yield.   Keywords: Compost, Decomposer and Pakchoy